ANALISIS PERSEDIAAN KAPORIT UNIT IPA CENDANA PADA PDAM TIRTA KENCANA SAMARINDA - Syaiful Hifni (OBOR: Oikonomia Borneo, 2019)
This study aims to determine the efficient amount of inventory costs by comparing the inventory management of the Cendana IPA Unit with inventory management using the Economic Order Quantity (EOQ) method at the Cendana IPA Unit at PDAM Tirta Kencana Samarinda. In this study using an analytical tool with the Economic Order Quantity (EOQ) method to find out the amount and cost of inventory efficiently, and assisted by other analytical tools, namely Safety Stock, Re Order Point, total ordering cost, total storage cost and total inventory cost. From the results of the analysis, it is known that inventory management using the Economic Order Quantity (EOQ) method is more efficient than the inventory management of the Cendana IPA Unit at PDAM Tirta Kencana Samarinda. The test results state that together the EOQ method can minimize inventory costs. Thus the proposed hypothesis can be accepted.